The Influence of Financial Literacy, Individual Confidence, and Peers on Students' Saving Behavior in Malang City - Moch Nurhidayat; Noviana Yaniar Suprajitno; Teresia Sensari Sartini (International Research and Development for Human Beings (IRDH), 2026)
This study aims to analyze the effect of financial literacy, individual self-efficacy, and peer influence on students’ saving behavior in Malang City. The research uses a quantitative approach with a survey method by distributing questionnaires to 100 student respondents. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing using t-test and F-test. The results show that partially, financial literacy does not have a significant effect on students’ saving behavior. This indicates that students’ financial knowledge has not been fully implemented in their daily financial behavior. Meanwhile, individual self-efficacy has a positive and significant effect on saving behavior, meaning that higher confidence in managing finances leads to better saving behavior. In addition, peer influence also has a positive and significant effect, indicating that the social environment plays an important role in shaping students’ financial habits. Simultaneously, financial literacy, individual self-efficacy, and peer influence significantly affect students’ saving behavior. This shows that saving behavior is influenced by a combination of knowledge, psychological, and social factors. The conclusion of this study is that saving behavior is more influenced by individual confidence and social environment rather than financial literacy alone. Therefore, it is necessary to improve self-awareness, motivation, and create a supportive social environment to encourage better financial management behavior.